2018
DOI: 10.1108/imefm-08-2017-0225
|View full text |Cite
|
Sign up to set email alerts
|

Islamic occasions and investor sentiment

Abstract: Purpose The purpose of this paper is to investigate whether the Islamic religious occasions can, through their impact on investor sentiment, affect returns in six Arab financial markets. Design/methodology/approach In this paper, the authors test the effect of the occasions of Hajj pilgrimage, Ramadan, Eid-al-Fitr, Mawlid and Ashura during the period of 2001-2016 on Saudi Arabia, Dubai, Kuwait, Egypt, Qatar and Bahrain financial markets. Three measures of investor sentiment are used: trading volume, high min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…Several attempts have been made to investigate the DoW effect on stock markets in different regions of the world. For instance, Jaffe and Westerfield (1985) analyzed a weekend effect in Australia, Japan, the UK and Canada stock markets. Wong et al (1992) examined the stock markets of Singapore, Malaysia, Hong Kong, Thailand and Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several attempts have been made to investigate the DoW effect on stock markets in different regions of the world. For instance, Jaffe and Westerfield (1985) analyzed a weekend effect in Australia, Japan, the UK and Canada stock markets. Wong et al (1992) examined the stock markets of Singapore, Malaysia, Hong Kong, Thailand and Taiwan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the best of our literature documentation (Aloui et al, 2016;Dash & Maitra, 2018;Jaziri & Abdelhedi, 2018), there is still academic debate over whether Islamic values moderate the sentiment-returns relationship, especially in an emerging market. Therefore, we contribute to the related literature gap.…”
Section: Model Developmentmentioning
confidence: 99%
“…Secondly, they showed that there is a significant positive change in the Islamic investor's emotion after "elhajj" pilgrimage and "Eid al el idha" holiday. For their part, Jaziri and Abdelhedi (2018) tested the impact of Islamic religious occasions on the investor's sentiment. The obtained results indicated a significant impact of the investor's sentiment on all the Arab financial markets in the first and second 10 days of Ramadan .…”
Section: Imefm 132mentioning
confidence: 99%